The Influence of Business Location Feasibility, Social Media Advertising and Product Innovation on Increasing Sales of Micro, Small and Medium Enterprises in The Culinary Sector at The Center Point of Indonesia Makassar City - Marhawati; Rahman, Nur Delima Novita; Mustari; Ampa, Andi Tenri; Rijal, Syamsul (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of business location feasibility, social media advertising and product innovation partially and simultaneously on increasing sales of culinary MSMEs at Center Point of Indonesia (CPI) Makassar City. This study employs quantitative research methodologies. The data collection techniques used were observation and interviews using questionnaires and documentation of activities. The population as well as the sample in this study were 50 culinary MSME business actors located at the Center Point of Indonesia (CPI). The employed data analysis techniques encompass multiple linear regression analysis, the F-test, the t-test, and the coefficient of determination. The results showed that business location feasibility, social media advertising and product innovation partially influenced the increase in sales of Culinary MSMEs at Center Point of Indonesia (CPI). Business location feasibility variables, social media advertising and product innovation simultaneously affect the increase in sales of Culinary MSMEs at Center Point of Indonesia (CPI)